Who are those guys? The profile of domestic violence perpetrators: financial situation, em-ployment and health status - Łukasik, Paulina; Karakuła-Juchnowicz, Hanna; Morylowska-Topolska, Justyna (Current Problems of Psychiatry, 2015)
Violence against women is a universal problem, appearing all around the world, with different frequency. The aim of this work was to investigate the prevalence of domestic violence in the study group and to present the profile of intimate violence perpetrators in terms of their financial situation, employment and health status. The study group comprised of 200 mature female patients visiting a family doctor in six primary health care centres in Lublin Province. Methods. Women’s Experience With Battering Scale (WEB) and a questionnaire designed by the authors of the study were used as screening tools for detecting whether the women were subject to intimate partner violence. Results and conclusions: The prevalence of intimate partner violence (IPV) in the study group was 41% during their lifetime and 26.5% during the last year. As many as 51% of the participants had positive WEB Scale scores, which indicates actual or threatened abuse. Most women reported that their current (81.8%) or former (11.4%) husbands were the perpetrators of domestic violence, compared to less than 7% of cohabiting partners. Regarding the violence perpetrators, over 80% of them used too much alcohol at the time of the study, while 75% of them had a past history of alcohol abuse; almost 66% were employed but 48.4% of them experienced financial problems; 19.3% had criminal records; 12.1% were diagnosed with epilepsy, 13.5% were affected by some type of mental disorder, and as many as 25.9% suffered head injury.